1986
DOI: 10.1007/bf00506514
|View full text |Cite
|
Sign up to set email alerts
|

Sodium regulation of agonist and antagonist binding to ?-adrenoceptors in intact and Ns-deficient membranes

Abstract: Agonist binding to various hormone receptors mediating adenylate cyclase inhibition is decreased by sodium ions. We studied the influence of Na+ on agonist and antagonist binding to beta-adrenoceptors in membrane preparations of guinea pig lung, S49 lymphoma wild-type cells (WT) and their Ns-deficient cyc- variants by measuring binding of the antagonist, [125I]iodocyanopindolol [( 125I]CYP). At 37 degrees C, sodium decreased the receptor affinity for the agonist, isoproterenol, in all three membrane preparatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…In contrast, there were no indications in the literature that Na + ions had a similar effect on β 1 AR. However, data on β 2 AR suggested Na + ions may be important for activity [42], particularly when considered in conjunction with data on the β 2 AR mutants D79A 2.50 or D79N 2.50 that showed decreased affinity of agonist binding and reduced receptor-mediated activation of G proteins [43], [44]. We therefore measured the affinities of agonist binding to membrane-bound wild-type β 1 AR in the presence of either 0 mM, 150 mM or 1 M NaCl.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, there were no indications in the literature that Na + ions had a similar effect on β 1 AR. However, data on β 2 AR suggested Na + ions may be important for activity [42], particularly when considered in conjunction with data on the β 2 AR mutants D79A 2.50 or D79N 2.50 that showed decreased affinity of agonist binding and reduced receptor-mediated activation of G proteins [43], [44]. We therefore measured the affinities of agonist binding to membrane-bound wild-type β 1 AR in the presence of either 0 mM, 150 mM or 1 M NaCl.…”
Section: Resultsmentioning
confidence: 99%
“…In vitro, increasing sodium concentration reduces beta adrenoceptor response (20,21). Further, intracellular sodium content may be higher in hypertensives (22), and is reduced with dietary sodium restriction (23).…”
Section: Discussionmentioning
confidence: 99%
“…For example, binding of isoproterenol to @-adrenoceptors of S49 mouse lymphoma cells was similarly regulated by Na+ in membranes prepared from wildtype (i.e. a,-containing) and a,-deficient cyc-cells (Minuth and Jakobs, 1986). Moreover, studies on GH4CI pituitary cells have shown that Na+ inhibited thyrotropin-releasing hormone binding only in membranes but not in intact cells (Hinkle and Kinsella, 1984).…”
Section: Discussionmentioning
confidence: 99%